AFETOS TRANSITÓRIOS: ROMANCES REALISTAS E UTOPIAS HOMONORMATI-VAS NO CINEMA QUEER CONTEMPORÂNEO - Daniel OLIVEIRA, Mestrando (Fonseca, Journal of Communication, 2023)
Based on a work of literature review, this paper investigates the main recurring aspects of contemporary queer cinema, specifically features starring and/or directed by LGBTQIA+ persons in the last decade. The starting point is a number of authors who, inspired by B. Ruby Rich’s work in characterizing the New Queer Cinema movement in the 1990s, set out to identify which political and aesthetic aspects stand out in the current queer filmography – and how they reflect the LGBTQIA+ community’s present moment.